Pengaruh Pemberian Dedak Padi Terfermentasi dalam Ransum terhadap Penampilan Puyuh Jantan Umur 2-7 Minggu - Agung Maramba Natar; Ni Ketut Sri Rukmini; Ni Ketut Mardewi (GEMA AGRO, 2023)
The purpose of this study was to determine the effect of giving fermented rice bran in the ration on the performance of male quail aged 2-7 weeks and to determine the level of fermented rice bran could produce the average initial body weight, body weight gain, final body weight, feed consumption and FCR ratio. The study was conducted using a completely randomized design (CRD) with 5 treatments and 3 replications. Each replication consisted of 3 male quails so that the number of male quails used was 45. As for the treatment as follows, the ration without the content of fermented rice bran as a control and the ration of fermented rice bran 5%, 10%, 15% and 20%. Parameters observed were initial body weight, weight gain, final body weight, feed consumption, and FCR (Feed Conversion Ratio). The data obtained were analyzed for variance. From the results of this study, the provision of fermented rice bran in commercial rations of male quail feed in the grower-finisher phase showed significantly different results (P<0.05) on final body weight, body weight gain, feed consumption, and FCR. Based on the results of this study, it is recommended that male quail breeders use fermented rice bran at a level of 20% in the ration because this level shows good results compared to the performance of male quail at a treatment level of 0% without fermented rice bran.